Measuring Plantar Tissue Stress in People With Diabetic Peripheral Neuropathy: A Critical Concept in Diabetic Foot Management. (September 2019) - Lazzarini, Peter A.; Crews, Ryan T.; van Netten, Jaap J.; Bus, Sicco A.; Fernando, Malindu E.; Chadwick, Paul J.; Najafi, Bijan
Excessive stress on plantar tissue over time is one of the leading causes of diabetic foot ulcers among people with diabetic peripheral neuropathy. Plantar tissue stress (PTS) is a concept that attempts to integrate several well-known mechanical factors into one measure, including plantar pressure, shear stress, daily weight-bearing activity, and time spent in prescribed offloading interventions (adherence). Despite international diabetic foot guidelines recommending the measure of each of these individual mechanical factors in people with neuropathy, only recently has technology enabled their combined measurement to determine PTS. In this article we review the concept of PTS, the mechanical factors involved, and the findings of pivotal articles reporting measures of PTS in people with neuropathy. We also discuss key existing gaps in this field, including the lack of standards to measure and report PTS, a lack of practical solutions to measure shear stress, and the lack of PTS thresholds that may indicate benefit or detriment to people with neuropathy. To address some of these gaps, we propose recommended clinical and research standards for measuring and reporting PTS in people with neuropathy. Last, we forecast future clinical, research, and technological advancements that may use PTS to highlight the importance of this critical concept in the prevention and management of diabetic foot ulcers.